Collaborative Learning with Application of Screen-based Technology in Physical Education - Gabriela Luptáková; Branislav Antala (Montenegrin Sports Academy, 2017)
Collaborative learning has been shown to be a useful tool for improving several social skills in students; however, it is very difficult to set up the initial conditions that guarantee its effectiveness. Since group projects are made for students and, most importantly, by students, we should not forget to take their opinions based on previous experience into consideration, which might increase the efficiency of their own learning. Therefore, the aim of the study was to investigate what secondary school students learn from and think about group projects in Physical Education. A total of 94 secondary school students (46 girls and 48 boys) participated in the study carried out in the 2015/2016 school year. The participants were given the assignment to create a video exercise, which they were working on in small groups in PE. A questionnaire was designed to investigate students' learning outcomes, participation, evaluation, and attitudes towards the project. Differences for selected categorical variables were determined using the Chi-square test. The majority of the students reported improvement in selected social skills and better relationships with their teammates. In addition, several significant differences in students' opinions with respect to age and gender were found.